Utilization and potential of natural materials in prostodontics: literature review: Pemanfaatan dan potensi bahan alam dalam bidang prostodonsia: tinjauan literatur - Fadhilah Auliyah Anisabakti; Yunita Indah Sari; Michelle Liemdier; Nur Huda Danial; Beatriz Trisna; Nur Fadillah Budianto; Nurmayanti; Acing Habibie Mude (Makassar Dental Journal PDGI Makassar, 2022)
Antibiotics and antifungals are needed in the patient's dentures because acrylic resin denture base can be a breeding ground for Streptococcus mutans and Candida albicans colonies. Indonesia has biodiversity consisting of thousands of plant species so that it becomes an opportunity for the development ofsecondary metabolites for the healthcare industry. Some natural materials can be used as antibiotics, anti-inflammatory, and antifungal. Antibiotics and antifungalsare needed in the patient's dentures be-cause acrylic resin denture base can be a breeding ground for S.mutans and C.albicans colonies. This literature review explains the utilization and potential of natural materials in prosthodontics. So, it is concluded that various active compounds such as fla-vonoids, alkaloids,saponins, steroids, tannins, essential oils, kabivetol, estrgiol, eugenol metileugenol, carvakrol, phenol, trape-zoid, ascorbic acid and others found in natural materials have antifungal, antibacterial, and anti-inflammatory properties.